Entrepreneurship and the Education of Future Teachers - Jelena Stamatović; Lidija Zlatić (Journal of Elementary Education, 2021)
Modern education needs include teachers who possess entrepreneurial competences. The subject of our study is entrepreneurship education in the field of teaching. We conducted semi-structured interviews with senior students of the Faculty of Education in Uzice (N=70). Entrepreneurship education can be realised using formal, non-formal and informal methods in higher education. The fundamentals of entrepreneurship are already represented in the existing curriculum, which cannot be deemed sufficient for systematised knowledge of entrepreneurship. Therefore, faculties of teacher education must be open to new models of activity and content organisation aimed at the development and encouragement of entrepreneurial competences among future teachers.